Návrh marketingového mixu společnosti - Kovářová, Vlaďka (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Bakalářská práce je zaměřena na marketingový mix společnosti STAVING Olomouc, s.r.o. Teoretická kapitola je věnována návrhům východisek marketingového mixu a popisuje jeho jednotlivé části. Analytická kapitola obsahuje rozbor marketingového mixu dané společnosti a marketingové analýzy. Návrhová kapitola obsahuje návrhy na zlepšení.

This bachetor thesis is focused on the marketing mix of the company STAVING Olomouc,l.t.d. The theoretical head of the thesis contains both the starting point of the marketing mix and the decription of its particular parts. The analytical head of the thesis contains the analysis of the marketing mix of the company and the marketing analysis. The proposal head conains proposals for improvement.
The Proposal of Company Marketing Mix
Keywords: marketing; marketingový mix; konkurence; mikroprostředí; makroprostředí; dotazníkové šetření; ruční mytí automobilů.; marketing; marketing mix; competition; microenvironment; macroenvironment; survey; advertising; hand-car-washing.